Chocolate and Embryo Implantation - Sevar, Raymond (Homœopathic Links, 2015)
Two infertile women in whom five apparently normal embryos formed by in vitro fertilisation (IVF) had failed to implant were treated with the homeopathic medicine Chocolate. Both women successfully implanted the next IVF embryo and gave birth to daughters.
Keywords: Infertility; Embryo implantation; In vitro fertilisation; IVF; Anandamide; Chocolate